17) 11.1
18) 21.4
19) 30.5
20) 16.5
21) 26.5
Answer:
3* (b+9) = 4
Step-by-step explanation:
b is the unknown number
Three times the sum of a number and 9 is 4.
3* (b+9) = 4
Answer: x = 4 and y = -3
Step-by-step explanation:
2x + 4y = -4
2x = -4 - 4y
x = -2 - 2y
Now that we have solved the first equation for x, we plug (-2 - 2y) into the other equation in place of x and then solve for y.
3(-2 -2y) + 5y = -3
-6 - 6y + 5y = -3
-y = 3
y = -3
Now that we know y, we plug it into the original equation and solve for x.
2x + 4(-3) = -4
2x + -12 = -4
2x = 8
x = 4
You can check the answer by plugging both x and y into either of the original equations.
Answer:
9
Explanation:
Hope it helps.. I got it right
Answer:
n = 19/18
Step-by-step explanation:
Given:
11/6 = n + 7/9
Find n
11/6 = n + 7/9
Subtract 7/9 from both sides of the equation
11/6 - 7/9 = n + 7/9 - 7/9
11/6 - 7/9 = n
(99-42) / 54 = n
n = 57/54
n = 19/18